Management Issues in Kedarnath Tragedy - Gupta, Ankur; Agrawal, Rajat (Journal of Advanced Research in Alternative Energy, Environment and Ecology; Vol 3 No 3&4 (2016): Journal of Advanced Research in Alternative Energy, Environment and Ecology, 2021)
This article aims to develop an in-depth perspective on management issues in Kedarnath tragedy that led to increase of death toll, loss of manpower and financial loss. Disasters cannot be avoided but the aftermath of disaster can be mitigated through effective disaster management by proper implementation of technology, contributing to disaster prevention and disaster preparedness in the concerned area. A massive devastation occurred in the Kedarnath town that led to the abjection of holy pilgrimage site due to combination of early rainfall, movement of southwest monsoon winds, and the excessive increase of water level in the Chorabari glacier on 15th and 16thJune 2013 due to heavy rainfall which devastated the town on 17thJune 2013 due to moraine dammed lake failure. Most of the agencies responsible for conducting research, and scholars who did research on Kedarnath tragedy, stated only scientific factors related to unusual weather condition near Kedarnath town responsible for devastation of holy town. There is abundance of technology available with government of India to make the pre-forecast for any flash food by flood forecasting stations governed by Central Water Commission (CWC), to detect the gathering of clouds in an area by Doppler Weather Radar which is capable enough to predict any cloudburst-like situation, and many more sophisticated methods to predict any disaster-like situation. The issue which arises over here is as to why India suffered to such a large extent in terms of loss of property, manpower and livestock in Kedarnath town even after it is fully equipped with flood forecasting methods and flood preparedness measures. The major issue that resulted in brutal effects of flash flood in Kedarnath was ineffective implementation of technology by inefficacious management.